Image saliency detection in wavelet domain based on the contrast sensitivity function - Ying-chun GUO; Yan-hong FENG; Gang YAN; Ming YU (Tongxin xuebao)
A method of high definition saliency detection based on contrast sensitive function and wavelet analysis was proposed in order to improve the resolution of saliency maps.Original image was filtered by contrast sensitive function in YCbCr space,which could simulate the contrast of human eyes; then wavelet decomposition was carried out in Y,Cb,and Cr three channels individually,low frequency and high frequency feature saliency maps were extracted and further combined to obtain saliency map in single channel; finally saliency maps in three channels were fused to the high resolution saliency map.Experiments result show that the saliency images have high resolution,well-defined boundaries,and whole highlight salient objects.